In vitro anti-inflammatory effects of naturally-occurring compounds from two Lauraceae plants - Coy-Barrera,Ericsson D. (2011)
The in vitro anti-inflammatory effects of seven known lignans and one dihydrochalcone isolated from the leaves of two Lauraceae species (Pleurothyrium cinereum and Ocotea macrophylla), were evaluated through the inhibition of COX-1, COX-2, 5-LOX and the aggregation of rabbit platelets induced by PAF, AA and ADP. (+)-de-4"-O--methylmagnolin 4 was found to be a potent COX-2/5-LOX dual inhibitor and PAF-antagonist (COX-2 IC50 2.27 µM; 5-LOX IC50 5.05 µM; PAF IC50 2.51 µM). However, all compounds exhibited an activity at different levels, indicating good anti-inflammatory properties to be considered in further structural optimization studies.